Religion and Social Cohesion in Vietnam: An Empirical Analysis of Community Dynamics - Ngoc, Tran Thi Thuy (Journal of Posthumanism, 2025)
This study investigates the role of religion in social bonding in Vietnam, with consideration of some key elements, like participation in religion, the degree of interfaith interaction, common cultural and ethical values, and support from the community leadership. The information was collected from 200 respondents in Hanoi, Hue, and Hoi An, cultural centers in Vietnam, by a structured questionnaire. The independent variables, such as social bonding, were modeled using a multivariate linear regression model. Findings indicated that community leadership support (β = 0.2218, p = 0.001) and shared cultural and ethical values (β = 0.252, p = 0.001) were the two strongest predictors for social bonding, which confirmed their very significant role in promoting trust and cooperation. The impact of religious participation (β = 0.163, p = 0.015) and interfaith interaction (β = 0.157, p = 0.014) was also statistically significant in a positive manner, underlining the importance of engaging in religious life and interfaith dialogue. The findings suggest that in Vietnam, which is one of the most multi-ethnic and multi-religious countries in the world, religion assumes a very important role in fostering community cohesion. These insights could provide meaningful lessons for policymakers, urban planners, and other stakeholders who are involved in the fostering of sustained social bonding through the lenses of community leadership and common cultural values. Addressing these major predictors can lead to building more inclusive and resilient communities in culturally heterogeneous environments.